2001
DOI: 10.1093/jaoac/84.5.1453
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Zearalenone Content in Cereals and Feedstuffs by Immunoaffinity Column Coupled with Liquid Chromatography

Abstract: The zearalenone content of maize, wheat, barley, swine feed, and poultry feed samples was determined by immunoaffinity column cleanup followed by liquid chromatography (IAC–LC). Samples were extracted in methanol–water (8 + 2, v/v) solution. The filtered extract was diluted with distilled water and applied to immunoaffinity columns. Zearalenone was eluted with methanol, dried by evaporation, and dissolved in acetonitrile–water (3 + 7, v/v). Zearalenone was separated by isocratic elution of acetonitrile–water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Recent studies about the metabolism of zearalenone by cell suspension cultures of maize (Zea mays), wheat (Triticum aestiVum), and different fungal species (Rhizopus sp., Thamnidium elegans, Mucor bainieri) showed that this metabolite is not only reduced to Rand β-zearalenol, but also conjugated to glucose (2,(6)(7)(8). This zearalenone-4-β-D-glucopyranoside (Figure 1) is not determined by current zearalenone analysis (9)(10)(11). However, gastrointestinal digestion releases the aglucone zearalenone (12), which can contribute to the development of a mycotoxicosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies about the metabolism of zearalenone by cell suspension cultures of maize (Zea mays), wheat (Triticum aestiVum), and different fungal species (Rhizopus sp., Thamnidium elegans, Mucor bainieri) showed that this metabolite is not only reduced to Rand β-zearalenol, but also conjugated to glucose (2,(6)(7)(8). This zearalenone-4-β-D-glucopyranoside (Figure 1) is not determined by current zearalenone analysis (9)(10)(11). However, gastrointestinal digestion releases the aglucone zearalenone (12), which can contribute to the development of a mycotoxicosis.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin and ochratoxin analyses were done according to AOAC Official Methods 991.31 [21] and 2000.03 [22], respectively. Zearalenone analysis was done as mentioned in the literature [23]. Deoxynivalenol analysis was done with DONPREP, which was supplied from R-Biopharm Rhöne Ltd., and deoxynivalenol analysis in cereal was done using water extraction.…”
Section: Analytical Methods For Mycotoxinsmentioning
confidence: 99%
“…These immunoassays were further amplified with fluorescent quantum dots [ 34 , 35 , 36 ], magnetic nanoparticles [ 37 ], or helical carbon nanotubes [ 38 ]. Alternatively, antibodies [ 24 , 36 , 39 , 40 , 41 , 42 , 43 , 44 ] or molecularly imprinted polymers [ 45 , 46 , 47 ] could be applied for affinity chromatography or pre-column sample purification prior to chromatographic analyses (HPLC, UPLC). Similarly, nanoparticle-assisted lateral flow immunochromatographic strips [ 48 , 49 ] were devised, occasionally with surface-enhanced Raman scattering detection [ 50 ].…”
Section: Introductionmentioning
confidence: 99%